A estruturação do futebol e seus elementos pedagógicos: uma visão a partir da praxiologia motriz - Marques Filho, Cesar Vieira (2017)
The work with soccer is inserted in different contexts, and it is often perceived that the pedagogical practice of the teacher/coach is supported by an empirical knowledge based on common sense. The present research aims at understanding the parameters that structure the dynamics of soccer from a scientific base, by using the knowledge of the Motor Praxeology. The methodology is characterized as propositional descriptive, of qualitative type. In this sense, I seek the understanding of the game's internal logic, characterizing the motor actions that emerge from it, in the context of cooperation and opposition interactions, present in all moments of the game. I analyzed the dynamics of the roles and sub-roles that the participants exercise, qualifying the understanding about soccer and proposing inputs for the teaching-learning-training process of this modality. In this sense, I aimed at elaborating a proposal that indicates basic and essential knowledge that will serve as a foundation for the teacher/coach who wishes to work with the teaching/training of soccer.